3D Print Polyaniline/Gelatin Hydrogels as Wearable Multifunctional Sensors. Issue 45 (1st December 2022) - Sun, Shuang; Hao, Feiyue; Maimaitiyiming, Xieraili
Abstract: Gelatin is a good biocompatible material. Polyaniline is a polymer compound that can conduct electricity when doped with phytic acid (Ph). However, there are few reports on PANI and gelatin hydrogels. In this paper, a new synthesis method of polyaniline (PANI) was developed, which greatly improved the gas sensitivity while maintaining the excellent quality of PANI. PANI and gelatin were composited into a unified 3D network. ANI synthesized phytic acid‐doped PANI and then mixed gelatin with it to make wearable 3D printed sensors. Multilayer structures prepared by 3D printing with PANI ink are free of build‐up. A PANI hydrogel sensor was fabricated using a 3D printing method with a stress sensing range of 0–899.8 MPa, a strain sensing range of 0–764.4 % sensitivity GF=1.4, and a TCR=−1.3 for temperature 8.4–29 °C. The sensor can accurately detect the motion of large strains in human knee joints and small strains in finger bending. In this study, a simple "green" method was used to convert inexpensive gelatin into a high‐performance multifunctional wearable sensor, which can be recycled and provided application prospects for sustainable and environmentally friendly biocompatible materials in the future. Abstract : A flexible wearable device was prepared by 3D printing. The flexible sensor can detect human strain, temperature and humidity. The sensor can generate different signals for different ammonia concentrations.